INFILTRATING UROTHELIAL CARCINOMA ALONG THE URINARY TRACT OF A YOUNG ADULT - Suryanti, Sri; Kharisma, Yuktiana; Tigor, Aaron (Indonesian Journal of Urology, 2021)
Objective: To present a rare case of infiltrating urothelial carcinoma along the urinary tract on a young adult. Case(s) Presentation: A 39 year old Asian male patient with > 20 pack-year smoking history, came to the hospital with a chief complaint of hematuria and flank pain since two weeks ago. Physical examination revealed Eastern Cooperative Oncology Group (ECOG) Performance Status 1, the right kidney was palpated, no tenderness on fist percussion. Abdominal ultrasound (USG) revealed 1.5 cm and 0.5 cm masses located in the urinary bladder. The CT scan show mass in the bladder was exophytic, > 3 cm in size, and occupying lesion was located on the right posteroinferior and left lateral bladder wall accompanied with dilatation of pelvic calyces and right ureter. Histopathology of the specimen revealed low-grade infiltrating urothelial carcinoma of bladder and right ureter. The pathological stage was pT2NxMx, The patient refused neoadjuvant chemotherapy and surgery. Four months after TURBT, he came with weakness and right flank pain. The patient consent to surgery and underwent the right nephroureterectomy. Histopathology of the specimen showed infiltrating urothelial carcinoma of right kidney, ureter, Gerota fascia with lymphovascular invasion (pT3NxMx). Discussion: Urothelial carcinoma (UC) is commonly arising in the urinary bladder, but it can develop along the urinary tract. Cigarette smoke contains a lot of carcinogenic agents and stimulates DNA damage. Conclusion: Upper tract urothelial carcinoma (UTUCs) is subset of UC with a poor prognosis. Cigarette smoking is the main risk factor that induces DNA damage.